4-Formylazetidin-2-one as a useful building block for the formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine - Kale, Ajaykumar S.; Sakle, Prathmesh S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
Stereoselective formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine is described starting from an enantiopure formyl-substituted P-lactam. Grignard reaction of the N-Boc-protected-beta-lactam carbonyl group, followed by further transformations, provides a common intermediate for xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine.
Keywords: azetidin-2-one; beta-lactam; Grignard reaction; Phytosphingosine; Sphingosine

Practical formal synthesis of D-(+)-biotin from 4-formylazetidin-2-one - Kale, Ajaykumar S.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
A practical synthesis of (3S,6R)-1,3-dibenzyltetrahydro-1H-furo[3,4-d]imidazole-2,4-dione, an important intermediate in the synthesis of biotin, from 4-formyl-3-mesyloxyazetidin-2-one has been achieved. Acid-catalyzed azetidin-2-one ring opening followed by a one-pot conversion of diamine hydrochloride to a cyclic urea and hydroxymethylene to chloromethylene by triphosgene to obtain (4S,5R)-methyl-1,3-dibenzyl-5-chloromethyl-2-oxoimidazolidine-4-carboxyl ate is the key step in this synthesis.
Keywords: azetidin-2-one; beta-Lactams; cyclization; Lactone; reduction